2004
DOI: 10.1063/1.1842862
|View full text |Cite
|
Sign up to set email alerts
|

Backscattering limitation for fiber-optic quantum key distribution systems

Abstract: We characterized backscattering effects in optical fiber using a photon counting technique and considered its implications for quantum key distribution (QKD). We found that Rayleigh (elastic) backscattering can put strong limitations on a two-way QKD system’s performance. Raman (inelastic) scattering can restrict the ability of wavelength multiplexing of a quantum channel with strong classical data channel(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 11 publications
0
59
0
Order By: Relevance
“…In fact, Subacius et al extensively investigated the backscattering in the fiber and its impact on the performance of a two-way QKD system. They concluded that for the two-way QKD system, a longer transmission and higher key rate are conflicting demands, even if the photon detector performance is improved [25]. Alternatively, the collision of crossing pulses in the fiber can be reduced by sending bursts of pulses spaced by long dead intervals and using a storage line in Alice's system, but this eventually reduces the effective key rate [14].…”
Section: Michelson Interferometer and Faraday Mirrors To Develop An Imentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Subacius et al extensively investigated the backscattering in the fiber and its impact on the performance of a two-way QKD system. They concluded that for the two-way QKD system, a longer transmission and higher key rate are conflicting demands, even if the photon detector performance is improved [25]. Alternatively, the collision of crossing pulses in the fiber can be reduced by sending bursts of pulses spaced by long dead intervals and using a storage line in Alice's system, but this eventually reduces the effective key rate [14].…”
Section: Michelson Interferometer and Faraday Mirrors To Develop An Imentioning
confidence: 99%
“…Recently, several commercial prototypes based on this system have been released [24]. Despite its usefulness, several drawbacks originating from two-way photon transmission have been pointed out [14,17,19,21,23,25]. For example, Ribordy et al…”
Section: Michelson Interferometer and Faraday Mirrors To Develop An Imentioning
confidence: 99%
“…It will significantly save the communication resource of the optical network. However, the influence of the Raman scattering and direct crosstalk will evidently increase the QBER and restrict the communication ability [20] , which can be observed in the field-test data below.…”
Section: Basic Qkd-link Devicementioning
confidence: 91%
“…In addition, a broad background is observed, arising from spontaneous Raman scattering in the silica glass of the fibre. This inelastic process exhibits equal scattering cross-sections in both the forward and reverse directions, thus transferring photons from the conventional channels into new frequency bands spread across the full fibre transparency window [21,22]. The QKD system used here has a nominal launch power level of −65 dBm and the FTTH network has a transmission loss of approximately 23 dB, resulting in a receive power of the quantum channel of around −88 dBm.…”
Section: Introductionmentioning
confidence: 99%